2018
DOI: 10.1177/1177180118764126
|View full text |Cite
|
Sign up to set email alerts
|

Pacific university graduates in New Zealand: what helps and hinders completion

Abstract: Increasing the numbers of Pacific Island students who graduate from New Zealand universities is important for the students' futures, their families, communities, and society in general. In the present study, Pacific graduates (N=365) who are participants in the Graduate Longitudinal Study New Zealand were asked to describe what factors helped or hindered their qualification completion. Graduates from all eight New Zealand universities were surveyed between July and December 2011. Pacific graduates identified e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…Regardless of tuakana-teina, whanaungatanga, Pasifika practices and other Māori health philosophies instigated as affirming learning approaches, the research by Theodore et al (2018), Equity in New Zealand university graduate outcomes: Māori and Pacific graduates, highlights that Māori and Pacific peoples are under-represented amongst New Zealand universities and their labour market outcomes are often associated with lower wages and under-representation in skilled professions. Boosting the success of Pasifika graduates has been, and continues to be, a priority and challenge for the New Zealand tertiary education sector.…”
Section: Indigenous Māori Learning Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…Regardless of tuakana-teina, whanaungatanga, Pasifika practices and other Māori health philosophies instigated as affirming learning approaches, the research by Theodore et al (2018), Equity in New Zealand university graduate outcomes: Māori and Pacific graduates, highlights that Māori and Pacific peoples are under-represented amongst New Zealand universities and their labour market outcomes are often associated with lower wages and under-representation in skilled professions. Boosting the success of Pasifika graduates has been, and continues to be, a priority and challenge for the New Zealand tertiary education sector.…”
Section: Indigenous Māori Learning Approachesmentioning
confidence: 99%
“…Similarly, family is perceived as a source of love and encouragement and expectations from family members help motivate students to be successful. Conversely, family responsibilities or commitments and issues were noted as having impacting students' completion (Theodore et al, 2018). However, Toumu'a and Laban's (2014) study found family to be a prominent influence because it is a key source of motivation for Pasifika students.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Education systems in New Zealand have consistently and historically underserved Pasifika peoples (Boon-Nanai, Ponton, Haxella, & Rasheeda, 2017;Chu, Glasgow, Rimoni, Hodis, & Meyer, 2013;McDonald & Lipine, 2012;Porter-Samuels, 2013;Reynolds, 2016;Teevale & Teu, 2018;Theodore et al, 2018). This underserving is an important issue for Pasifika people because we connect our community wellness with educational outcomes (Pasefika Proud, 2017;Samu, 2010).…”
Section: Pasifika and Education In New Zealandmentioning
confidence: 99%
“…These challenges included increases in Pasifika youth delinquency (Borrero, Yeh, Tito, & Luavasa, 2010;Yeh, Borrero, Tito, & Petaia, 2014) and incarceration (Shepherd & Ilalio, 2016), disproportionate representation of Pasifika with serious health issues (Hawley & McGarvey, 2015), and concerns about the academic achievements of Pasifika students (Coxon, Anae, Mara, Wendt-Samu, & Finau, 2002;Ferguson, Gorinski, Samu, & Mara, 2008). In New Zealand, more authorities and academic institutions installed guidelines for Pasifika-related services, engagement and research (i.e., Airini et al, 2010;Anae, Coxon, Mara, Wendt-Samu, & Finau, 2001; Health Research Council of New Zealand, 2014; University of Otago, 2011), and the numbers of Pasifika students enrolled in postgraduate research gradually increased (Tertiary Education Commission, 2017; Theodore et al, 2018). In these circumstances, Pacificand Pasifika-specific approaches to academic inquiry emerged, some building on the work of the scholars mentioned above, and others completely new in conceptualisation.…”
Section: The Emergence Of a Pacific Research Paradigmmentioning
confidence: 99%